Wider range of crops grow under Sahelian tree - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Research has confirmed that farmers in the Sahel can increase the range and yields of their crops if they plant them under a Faidherbia albida (Acacia albida) tree. This tree has been traditionally conserved in the region, because its benefits have...